A study on factors that influence employees motivation among USM Kampus Kesihatan Kubang Kerian / Raja Mohamad Nasharudie Raja Hassan - Raja Hassan, Raja Mohamad Nasharudie (2014)
This research study has been conducted to discover the factors that influence employee motivation among USM Kampus Kesihatan staff. The main objective of this research is to find the most significant factor that influence employee motivation. There are three variables was involve in this study in order to measure the most factors, the level of factors and the relationship toward employee motivation which are promotion, working condition and job security. The researcher used some of techniques to analysis these variables are Descriptive analysis, Correlation of Determination and Regression analysis. Then, based on correlation coefficient result, the moderate relationship between employees motivation are promotion and working condition. The values for both variables are 0.6 and 0.50. Furthermore, the relationship for job security with employee motivation is moderate also. This is because the value for the variable is 0.471. More than that, according to regression analysis results, it shows that promotion is the most factors that influence employee motivation where got the highest beta value is .565 compared to the other variables. However, the result showed that both of the variables which are working condition and job security are not significant and not influence toward employee motivation. But overall, it still can be consider significant because R2 more than 0.5. This information is also helpful to determine whether the variables influence employee motivation. The results showed that independent variables namely promotion had significant influence with employee motivation while working condition and job security had no significant influence with employee motivation.